An integrative review: High-performance work systems, psychological capital and future time perspective. Issue 4 (11th April 2019) - Abubakar, A. Mohammed; Foroutan, Taraneh; Megdadi, Khaled Jamal
Abstract : Purpose: Psychological capital (PsyCap) and future time perspective (FTP) are ambassadors of positivity among incumbent employees in organisations. However, remarkably little is known regarding the effectiveness of high-performance work systems (HPWS) in nurturing these constructs. The purpose of this study is to contribute and provide a complete frame of reference linking HPWS to PsyCap and FTP. Design/methodology/approach: A synthesis analysis of existing literature was carried out to formulate managerial and practical propositions. Findings: Drawing on the conservation of resources theory, affective events theory and Job Demands-Resources (JD-R) model, the present study proposes a research framework that links HPWS, FTP and PsyCap, with possible mediation effect of FTP in HPWS–PsyCap relationship and PsyCap in HPWS–FTP relationship. Practical implications: Although this paper did not test the model empirically, it offers important practical implications in terms of PsyCap and FTP perception development through HPWS practices. Originality/value: A set of propositions that explain the relationships between the study variables is presented to enrich the understanding with organisation's HRM practices and its possible impact on employees.